A Bending Passive RFID Tag as a Sensor for High-Temperature Exposure - Zahangir Khan; Xiaochen Chen; Han He; Adnan Mehmood; Johanna Virkki (International Journal of Antennas and Propagation)
This paper introduces a prototype of a low-energy high-temperature exposure sensor, which is a temperature-sensitive passive UHF RFID tag that bends forward when exposed to warm air. This “Bending Tag” design is based on a simple dipole antenna fabricated from an electro-textile material. The antenna has a 3D-printed substrate, which is constructed from a commercial Thermo Reactive Filament that gets soft when exposed to 50°C for 30 seconds, causing the tag to bend forward and curve. The sensor tag initially has a read range of more than 6 meters throughout the global UHF RFID frequency band. After bending, there is a significant decrease in the read range (to around 2–3 meters), which is caused by the changed backscattered power of the sensor tag. In an office environment, the backscattered power changes from −36 dBm to −43 dBm. The change in a sensor tag-reference tag system as dP% is approximately 70%. Based on these initial results, our bending tag can be further developed to work as a cost-effective low-energy sensor for monitoring high-temperature exposure.